A carbene-yielding amino acid for incorporation into peptide photoaffinity reagents. - Shih, L; Bayley, H (1985)
3-[p-[3-(Trifluoromethyl)-3H-diazirin-3-yl]phenyl]alanine has been prepared in 10 steps from p-bromobenzyl alcohol. The alcohol was converted to 3-(alpha-iodo-p-tolyl)-3-(trifluoromethyl)-3H-diazirine, which was used to alkylate N-(diphenylmethylene)glycine ethyl ester. After deprotection the amino acid was obtained with an overall yield of 18%. The D- and L-isomers of 3-[p-[3-(trifluoromethyl)-3H-diazirin-3-yl]phenyl]alanine have also been resolved, and 3-[p-[3-(trifluoromethyl)-3H-diazirin-3-yl]phenyl]alanine labeled with tritium has been prepared. The advantages of using this amino acid as a building block for peptide photoaffinity reagents is discussed.